DANGERS THAT OCCUR IN THIS VEHICLE WHEN MOVING TO THE CONNECTING ROUTES OF DAMAS CARS - Yokubov Saydorib Odiljon ugli; Mukimova Davlatkhon Karimovna (Лучшие интеллектуальные исследования, 2024)
Abstract. Technical operation of Damas is one of the main systems of road transport, which determines its development, improvement and place in the transport system of the Republic. The main objectives of the technical operation of the car are its potential features, ie operational reliability, reduction of maintenance and repair costs, reduction of downtime, efficient transportation and reduction of transportation costs, environmental friendliness. To solve these problems, it is necessary to study the laws that change the technical condition of the car and its components under the influence of various factors. This will allow you to study the laws, develop and apply methods of keeping the car in a technically ready condition.